2017
DOI: 10.1111/jfbc.12445
|View full text |Cite
|
Sign up to set email alerts
|

Apple phlorizin supplementation attenuates oxidative stress in hamsters fed a high-fat diet

Abstract: Phlorizin from apple peel has been used as a nutrient for more than 100 years. The present study investigated the effects of phlorizin on the antioxidant capacity and the antioxidative mechanisms in hamsters fed high-fat diet supplemented with phlorizin (0.3, 0.6, and 0.9%). Results showed that phlorizin increased the antioxidant enzyme activities and reduced the malondialdehyde content in plasma, liver, heart, and kidney that might arise from the higher mRNA levels of CuZn-superoxide dismutase, Mn-superoxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…These results implied that phlorizin alleviated the oxidative stress induced by H 2 O 2 by upregulating the related activities of antioxidant enzymes. This phenomenon was consistent with that in previous study showed that phlorizin exerted antioxidative effect by regulating the activities of antioxidant enzymes (Wang et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…These results implied that phlorizin alleviated the oxidative stress induced by H 2 O 2 by upregulating the related activities of antioxidant enzymes. This phenomenon was consistent with that in previous study showed that phlorizin exerted antioxidative effect by regulating the activities of antioxidant enzymes (Wang et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidants work by scavenging the free radicals, thereby inhibiting the activity of ROS. The antioxidants including endogenous antioxidant enzymes such as SOD, CAT, and exogenous dietary antioxidants such as vitamins C and E are essential defense anchors (Wang, Sun, Rehman, Shen et al, 2017). In the present study, the activities of SOD and CAT in fruit flies fed different dosages of phlorizin increased (Figure 2); 2.0 mg/ml phlorizin could significantly increase the CuZnSOD, MnSOD, and CAT enzyme activities.…”
Section: Discussionsupporting
confidence: 52%
“…MDA is a major oxidative degradation product of membrane unsaturated fatty acids. The level of MDA, which indicates the degree of lipid peroxidation, is an oxidative stress marker (Wang, Sun, Rehman, Wang et al, ). The present study demonstrated that phlorizin treatment could reduce the MDA level in fruit flies in vivo compared with that of the control group (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our previous study showed that phlorizin supplementation attenuates serum and liver oxidative stress by increasing SOD, CAT, GSH-PX, and T-AOC activity and reduces the MDA content by promoting the gene expression of Nrf2 in hamsters fed with HFDs. 8 However, there is an intimate association between inflammation and redox alteration. 36 Researchers have found that a dysfunction in the Nrf2 system is related to the initiation of inflammation, which, in turn, promotes ROS production, leading to redox imbalance by triggering redox-sensitive transcription factors and signal transduction pathways, further leading to obesity and consequent metabolic aberrances.…”
Section: Discussionmentioning
confidence: 99%